Phytochemical constituents and biological activities of Erythrina indica - Amir, Faheem; Yam, Wan Sinn; Koay, Yen Chin (European Journal of Chemistry, 2011)
Erythrina indica commonly known as Coral tree has been widely used in Indian traditional medicine for treating common ailments such as asthma, arthritis, diarrhoea, fever, inflammation and leprosy. Certain phytochemical constituents such as: alkaloids, aliphatic fatty acids, alkaloids have also been reported. A wide range of medicinal formulations have been developed from E. indica that exhibit analgesic, antiarthritic, anti-hypertriglyceridemia, anti-inflammatory and muscle relaxing effects. This review summarizes the phytochemical investigations and pharmacological activities of E. indica.